Feasibility and Preliminary Efficacy of Isradipine During Outpatient Buprenorphine Stabilization and Detoxification: A Pilot Randomized, Placebo-Controlled Trial. (November 2020) - Kumar, Nihit; Mancino, Michael J; Thostenson, Jeff D; McGaugh, Janette; Oliveto, Alison H
Background: Given the immense burden of the widespread use of opioids around the world, exploring treatments that improve drug use outcomes, and craving and withdrawal measures in individuals with opioid use disorder is crucial. This pilot study examined the feasibility and preliminary efficacy of the L-type calcium-channel blocker isradipine (ISR) to improve drug use outcomes, and craving and withdrawal measures during buprenorphine (BUP)/ISR stabilization and subsequent taper in opioid-dependent individuals. Methods: Participants were stabilized on BUP sublingual tablets within the first 2 days of week 1, were then randomized and inducted on either ISR or placebo, gradually increasing the dose over the next 2 weeks, followed by a 10-day BUP taper during weeks 5-6, and ISR/placebo taper during weeks 7 to 8. Assessments included thrice-weekly measures of craving and withdrawal, as well as vital signs and urine drug screens. Medication compliance was assessed by monitoring number of missed clinic visit days. Results: Baseline characteristics of participants (n = 25; 60% male, 96% Caucasian, 48% employed, mean age 32.8 years) did not differ significantly between treatment groups (isradipine, n = 11; placebo, n = 14). During the stabilization phase (n = 19), ISR participants had significantly lower rates of illicit opioid-positive urines (treatment × visit: t  = -2.16, P  = 0.03), as well as reduction in craving intensity ( t  = –2.50, P  = 0.01), frequency ( t  = –3.43, P  < 0.01) and duration ( t  = –2.51, P  = 0.01). ISR was well tolerated with mild adverse effects. Conclusions: This study was likely underpowered due to being a pilot trial. Although preliminary results suggest ISR may improve BUP-assisted treatment outcomes, concerns about high number of exclusions (n = 11 during taper phase) based on cardiovascular measures as well as ISR-induced changes in vital signs with the immediate release formulation may limit the feasibility of this approach. Trial Registration: Clinicaltrials.gov identifier NCT01895270. Registered 10 July 2013, https://clinicaltrials.gov/ct2/show/NCT01895270?id=NCT01895270&draw=2&rank=1